ECONOMIES OF THE INTERNET III: SPHERES - Kruse, Holly; O’Hallarn, Brendan; McKnight, John Carter; Tekkobe, Cindy; Shepherd, Tamara; Shtern, Jeremy (Association of Internet Researchers, 2015)
The internet has increasingly been conceptualized as a space of economic activity. This contemporary imaginary has been particularly influenced by insights from the school of Autonomist Marxism in the foundational work of Tiziana Terranova and through the dominance of Christian Fuchs’ application of Marxist economic concepts. While this has generated great insight into the political economy of the internet, and in particular allowed for the conceptualization of user activity as labor, this approach is only one paradigm for considering the economic activities and implications of the internet. For internet research, there is also the need to move beyond the long schism between political economy and cultural studies as we try to understand user activity that is socially and affectively rich, but emerges from commercial contexts. This series of panels proposes to expand the exploration of the internet as an economic construct in a number of directions. It pluralizes the definition of “economy”, expanding it from the strictly fiscal to include other economies such as the moral, (sub-) cultural, affective, queer, or libidinal (to name merely a few). Various papers propose different economic models for understanding the interactions within and between these various economies. They also expand the range of actors and economic contexts associated with the internet, drawing attention to the intersections of race and gender in particular. The goal of these papers across the various sessions is to expand our imaginary of the internet economy.The internet is a diverse place in which a diverse range of activities take place, both paid and unpaid. However this complexity is not always represented in studies of economic activity which often abstract from specific practices of users and industry workers in favor of proving an economic model, or focus on the obvious examples of SNS use by a de-racialized, de-gendered, de-sexed consuming subject. This has left gaps in our understanding of internet economies, whether that be of particular economic activities or networks, or of how social status inflects and informs economic activity both within the paid workplace and in the sphere of leisure. The papers in this panel explore little-considered arenas of online economic activity and economic actors, working to develop the plurality of how we conceptualize the internet as an economic assemblage. They also demonstrate how economic spheres cannot be analyzed discretely from social contexts.The first two papers engage with sport, an important arena of economic activity that is only rarely studied as a mediated cultural form. The first speaker explores the relationship between media technologies and the extremely lucrative horseracing and online gaming industries. The paper outlines the history of horseracing and wagering and their embedding in growing leisure economies, but also links that growth to changes in information and communication networks, including networked computers and the internet as we now know it. This paper goes on to explore how the online horseracing economy at times exemplifies and other times challenges our assumptions about online activity, in particular the ways in which class and gender intersect in this over-looked arena.The second speaker investigates the relationship between sport, Twitter and the informational economies of the public sphere. Examining mediated sports events such as the 2011 revelations of serial sex abuse by Penn State football coach or the suspension of Baltimore Ravens player Ray Rice, this analysis reflects on how, despite the potential of Twitter to amplify debate in negative ways, it also functions as a site for deliberative democracy. This paper explores the informational economy of the Habermasian public sphere generated in the discussions of sport on Twitter.The third speakers discuss the complex context of alternative currency system Mazacoin, claimed to be the “official tribal currency” of the Oglala Sioux Tribe and developed with the imprimatur of a sovereign governing body. This study examines forums related to this cryptocurrency, analyzing the boundary and identity work undertaken by a variety of stakeholders as they negotiate the intersection of personal, cultural and economic values in the development and implementation of the financial technology.The final paper enters into the sphere of paid work, exploring the labor of an emerging set of actors in digital media’s economy, digital strategists. As a new profession responsible for combining advertising, marketing, branding and public relations, the cultural intermediaries who do this work are not only responsible for setting tastes but are engaged in position-taking relating to their economic and social role. Based in a series of interviews with Canadian digital strategists, this study identifies the specific ways in which these actors’ conceptualize their labor’s contribution to social media’s economics. This paper, like the others in this panel, explores the ways in which the lifeworlds of workers and consumers are entwined with fiscal value creation.